Aid, ethics, and the Samaritan's dilemma: strategic courage in constitutional entrepreneurship. Issue 2 (18th August 2015) - SKARBEK, EMILY C.
Abstract: Private constitutional rules can mitigate the Samaritan's Dilemma, a widespread cause of failure of aid and humanitarian efforts. To understand how private organizations can adopt rules that help overcome this dilemma, I provide evidence on an association formed to govern poor relief in urban Chicago from the 1850s to 1880s. I show how a particular set of shared ethical values led to the adoption of constitutional rules governing the organization. I then show that these rules were specific in their ability to mitigate the Samaritan's Dilemma problem inherent to administering aid. The argument advances the understanding of private institutional structures by demonstrating how rules can be designed in the private spheres to solve specific social dilemmas that plague state-led efforts to achieve similar goals.